Pesticide residue profiles, dietary risk assessment, and mitigation strategies in citrus production systems of Pakistan - Muneer Abbas; Akbar Hayat; Sohaib Afzaal; Muhammad Ghayoor Husnain; Hira Tariq; Fiaz Hussain; Niaz Hussain; Muhammad Saleem; Dilbar Hussain; Aleena Alam; Wang Dongze; Sohail Abbas (Food Control, 2026)

Evaluation of the Air Pollution Mitigation Potential of Some Roadside Plants for Urban Forest Management - Mahrukh; Sohaib Muhammad; Muhammad Tayyab; Ali Ahmad; Zaher Uddin Babar; Nahaa M. Alotaibi; Muhammad Bilal; Amr Elkelish; Iqra Parvaz; Bushra Munam; Summiya Faisal; Muhammad Hasnain (Water, Air, & Soil Pollution, 2026)

Scheduling operation coordination of multi energy virtual power plant integrating thermal comfort and demand response flexibility approaches - Muhammad Sohaib Azeem; Xueping Pan; Xiaorong Sun; Jinpeng Guo (Energy and Buildings, 2026)

An analysis of impact of soil co-pollution with lead and traditional/biodegradable microplastics on growth characteristics of maize (Zea mays L.) - Muhammad Kashif Irshad; Saba Saleem; Jamilur R. Ansari; Ali Noman; Muhammad Aqeel; Mohamed O. Alshahrani; Modhi O. Alotaibi; Muhammad Sohaib Irshad; Sang Soo Lee (Journal of Environmental Sciences, 2026)

Machine learning and response surface modeling for predicting strength loss of alkali-activated materials exposed to aggressive environment - Munir Iqbal; Sohaib Nazar; Muhammad Hasham Kashif; Muhammad Ashraf; Haji Sami Ullah (Innovative Infrastructure Solutions, 2026)

Synergistic Effects of Maize Volatiles on Pheromone Trap Captures of the Fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) - Fida Hussain Magsi; Amees Ullah; Yihui Ma; Guoping Li; Jianrong Huang; Muhammad Sohaib; Songke Li; Xincheng Zhao; Hongqiang Feng (Journal of Chemical Ecology, 2026)

Antimicrobial Plant Protein Patatin: Identification and In-Silico Analysis Through Phylogenetics and Molecular Docking - Sarah Tariq; Binish Khaliq; Hina Shaheen; Ahmad Riaz; Sumaira Rubbani; Muhammad Sajid Hamid Akash; Amjad Hussain; Muhammad Imran; Muhammad Arslan Javed; Ahmed Akrem; Sohaib Mehmood; Sajjad Azam (Agricultural Research, 2026)

The AI revolution in sustainable food processing: From process optimization to a circular bioeconomy - Asad A. Zaidi; Aisha Jilani; Muhammad Asif; Asim Laeeq Khan; Sohaib Z. Khan (Food and Bioproducts Processing, 2026)

Precision harvest: path to genetically modified organism-free crops with CRISPR by 2035 - Sunny Ahmar; Ruixiang Zhang; Pouneh Pouramini; Anna Janeczko; Muhammad Sohaib Shafique; Marcin Rapacz; Rodrigo S. Reis; Qinlong Zhu; Goetz Hensel; Ewa Pociecha (Trends in Plant Science, 2026)

The plastisphere as an engine of environmental change: Impacts on biogeochemical cycling and pollutant fate - Syed Shabi Ul Hassan Kazmi; Muhammad Azeem; Hafiz Sohaib Ahmed Saqib; Zaher Mundher Yaseen; Gang Li (Current Opinion in Environmental Science & Health, 2026)

Pollutant-driven humification of dissolved organic matter fails to mitigate the chronic toxicity of tire-wear contaminants in freshwater bioindicator - Syed Shabi Ul Hassan Kazmi; Qiao Xu; Hafiz Sohaib Ahmed Saqib; Muhammad Azeem; Paolo Pastorino; Damià Barcelò; Qiao Yang; Gang Li (Chemical Engineering Journal, 2026)

Hooves, herbs and heritage: ecological insights into the cultural and ethnoveterinary use of Bhagwanpura forest flora in livestock systems - Saima Khalid; Sohaib Muhammad; Ali Ahmad (Genetic Resources and Crop Evolution, 2026)

Sedimentology and biostratigraphy of the Cretaceous–Paleocene successions in Northern Pakistan: evidence from the Hazara, Kala Chitta, Potwar, and Kohat Basins - Syed Kamran Ali; Hafiz Sohaib Bashir; Asim Qadir; Muhammad Saleem Mughal; Khurram Iqbal; Abrar Niaz; Khawaja Umair Majeed (Carbonates and Evaporites, 2025)

Influence of cationic, anionic, and non-ionic surfactants on in-situ growth of polyaniline on alumina ceramic membranes for the effective crude oil-in-water emulsion separation: Experimental and machine learning approaches - Muhammad Saad Khan; Umair Baig; Abdul Waheed; Sohaib Abdelazem; Isam H. Aljundi (Desalination, 2025)

Modeling and thermoeconomic analysis of new polygeneration system based on geothermal energy with sea water desalination and hydrogen production - Wulaer Shaersaikai; Tuhuo Jia; Abdellatif M. Sadeq; Manoj Kumar Agrawal; Taseer Muhammad; Sohaib Tahir Chauhdary (Desalination, 2025)

A Potent Plant-Derived Chitinase: Structural Informatics and Insecticidal Activity against Helicoverpa armigera - Shah Rukh; Ahmed Akrem; Qamar Saeed; Sohaib Mehmood; Nosherwan Adil; Tazeen Rao; Muhammad Nasir; Uzma Ishaq; Aqal Zaman; Najeeb Ullah; Mohibullah Shah (Cell Biochemistry and Biophysics, 2025)

HIV mortality trends among the United States population, from 1999–2023: a CDC wonder database study - Abuoma Cherry Ekpendu; Muhammad Sohaib Asghar; Afsana Ansari Shaik; Muhammad Zain Khalid; Maria Duharte; Luis Duharte-Vidaurre; Moustafa Hegazi; Chad K. Brands (Infectious Diseases, 2025)

RbcLa marker based identification and phylogenetic analysis of Kasuri methi (Trigonella foenum-graecum L.): a native plant of Kasur district of Punjab (Pakistan) - Bin Yameen; Wasim Abbas; Muhammad Umer Farooq Awan; Aisha Tahir; Sohaib Mohammad; Muhammad Shoib (Genetic Resources and Crop Evolution, 2025)

Co-production and enhancement of biogas and biohydrogen by optimizing NaOH-urera pretreatment conditions for kitchen waste - Asad A. Zaidi; Sohaib Z. Khan; Hamad Almohamadi; Mohammad Rehan; Muhammad Abdul Qyyum (Process Safety and Environmental Protection, 2024)

Correction: Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Microplastics in agroecosystems: Soil-plant dynamics and effective remediation approaches - Muhammad Tayyab; Syed Shabi Ul Hassan Kazmi; Paolo Pastorino; Hafiz Sohaib Ahmed Saqib; Zaher Mundher Yaseen; Muhammad Sajid Hanif; Waqar Islam (Chemosphere, 2024)

Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Advanced photocatalysis as a viable and sustainable wastewater treatment process: A comprehensive review - Muhammad Ahtasham Iqbal; Sumia Akram; Shahreen khalid; Basant Lal; Sohaib Ul Hassan; Rizwan Ashraf; Gulmira Kezembayeva; Muhammad Mushtaq; Nurzhan Chinibayeva; Ahmad Hosseini-Bandegharaei (Environmental Research, 2024)

Improving urban road infrastructure analysis and design using an integrated BIM-GIS and traffic microsimulation framework - Mohammad Sohaib; Aaqib Najeeb; Muhammad Umair; Muhammad Arsalan Khan; Muhammad Umer Zubair; Zulqarnain Jehan; Afaq Khattak (Innovative Infrastructure Solutions, 2024)

IoT-based agriculture management techniques for sustainable farming: A comprehensive review - Hammad Shahab; Muhammad Iqbal; Ahmed Sohaib; Farid Ullah Khan; Mohsin Waqas (Computers and Electronics in Agriculture, 2024)

Thermo-economic-environmental analysis of a sustainable heat integration design for biomass-fueled power plant using integration of CCHP and sweater desalination application - Tirumala Uday Kumar Nutakki; Manoj Kumar Agrawal; Sohaib Tahir Chauhdary; Sayed Fayaz Ahmad; Mohamed Ayadi; Elmonser Hedi; Taseer Muhammad; Fuxin Xiao (Desalination, 2024)

Predicting ambient PM2.5 concentrations via time series models in Anhui Province, China - Ahmad Hasnain; Muhammad Zaffar Hashmi; Sohaib Khan; Uzair Aslam Bhatti; Xiangqiang Min; Yin Yue; Yufeng He; Geng Wei (Environmental Monitoring and Assessment, 2024)

Harnessing probiotics and prebiotics as eco-friendly solution for cleaner shrimp aquaculture production: A state of the art scientific consensus - Muhammad Noman; Syed Shabi Ul Hassan Kazmi; Hafiz Sohaib Ahmed Saqib; Usama Fiaz; Paolo Pastorino; Damià Barcelò; Muhammad Tayyab; Wenhua Liu; Zhen Wang; Zaher Mundher Yaseen (Science of The Total Environment, 2024)

Impact of Various Combinations of Organic and Inorganic Fertilizers on Fruit Production and Quality of ‘Kinnow’ Mandarin (Citrus reticulata Blanco.) - Muhammad Asim; Faisal Hayat; Tehseen Ashraf; Fakhara Khanum; Juan Li; Yang Peng; Yanxiao Ma; Shahid Iqbal; Ummara Khan; Sitwat Riaz; Panfeng Tu; Fiaz Hussain; et al. (Applied Fruit Science, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Microbial activity, community composition and degraders in the glyphosate-spiked soil are driven by glycine formation - Sohaib Aslam; Muhammad Arslan; Karolina M. Nowak (Science of The Total Environment, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

DNA metabarcoding reveals evidence of inter- and intra-guild predation by Scylla paramamosain in a marine ecosystem - Hafiz Sohaib Ahmed Saqib; Ye Yuan; Syed Shabi Ul Hassan Kazmi; Muhammad Tayyab; Zifei Xiang; Mhd Ikhwanuddin; Hongyu Ma (Frontiers in Marine Science, 2023)
Introduction Crustacean predators exhibit diverse trophic interactions across various habitats in aquatic ecosystems. To assess their ecological roles, it is essential to understand their complete dietary spectrum. Recently, DNA-based techniques such as DNA metabarcoding and high-throughput sequencing have provided insights into trophic networks and their response to environmental drivers. Methods In this study, we used these methods to investigate the impact of salinity gradients on the trophic networks of mud crabs (Scylla paramamosain) in marine ecosystems. Results Our results revealed that mud crabs prey on a wide range of taxa, including crabs (other than the host species), fish, shrimps, and other prey factions. Salinity gradients had a significant influence on the specific prey items, such as high predation on Metapenaeus, and Trigonopterus species in high salinity sites. Notably, crabs exhibited a greater infestation of Portunion parasites in environments with high salinity levels, in contrast to environments with lower salinity levels. Ordination analysis showed that mud crabs adapt their diet according to environmental constraints. Discussion Furthermore, the results indicate that mud crabs showed opportunistic predation behavior as they were observed preying on other Portunidae species sharing the same trophic guild. Overall, these findings demonstrate the dietary plasticity and associated parasite infestation of an important crustacean predator, and provide evidence that environmental changes may affect incidences of the associated parasites as well as the specific predator-prey interactions indirectly through fluctuations in marine ecosystems.

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Assessment of heavy metals and associated oxidative stress in occupationally exposed workers from Bannu and Karak Districts in Pakistan - Kaleem Khan; Muhammad Tariq Rafiq; Aziz-Ur-Rahim Bacha; Iqra Nabi; Muhammad Irshad; Faridullah Faridullah; Muhammad Younas; Muhammad Daud Khan; Rukhsanda Aziz; Muhammad Amin; Awais Arifeen; Sohaib Aslam; et al. (Environmental Geochemistry and Health, 2023)

Potassium-Nitrogen Ratio Improved Cotton Yield by Regulating Antioxidant Metabolism Under a New Cropping Model for the Yangtze River Valley of China - Saif Ali; Abdul Hafeez; Xiaolei Ma; Shahbaz Atta Tung; Muhammad Sohaib Chattha; Shoaib Ahmad; Adnan Noor Shah; Guozheng Yang (Journal of Soil Science and Plant Nutrition, 2023)

Potential Breeding Strategies for Improving Salt Tolerance in Crop Plants - Muhammad Afzal; Salah El Sayed Hindawi; Salem Safer Alghamdi; Hussein H. Migdadi; Muhammad Altaf Khan; Muhammad Usama Hasnain; Muhammad Arslan; Muhammad Habib ur Rahman; Muhammad Sohaib (Journal of Plant Growth Regulation, 2023)
Salinity is one of the significant abiotic stresses that negatively affect plant production processes, growth, and development, which ultimately reduce yield. Plants adapt specific mechanisms to withstand saline conditions and activate diverse salt tolerance genes to counter osmotic and oxidative stresses induced by salinity. Genetic development in salinity tolerance is quite complex, while advancement has made less progress than expectation over the past few decades. Generating an explosion of genetics- and genomics-related information and technology in recent decades pledge to deliver innovative and advanced resources for the potential production of tolerant genotypes. Despite considerable progress in defining the primary salinity tolerance mechanisms, main obstacles are yet to be solved in the translation and incorporation of the resulting molecular knowledge into the plant breeding activities. Diverse approaches are proposed to enhance plant breeding efficacy to increase plant productivity in saline environments. Understanding the genetics of salt tolerance is a difficult task because multiple genes and pathways are involved. Important advances in tools and methods for updating and manipulating plant genomics knowledge provide detailed insights and dissect the salinity tolerance mechanism accomplished by the breeding goals. Genome-wide analyses (GWA) identify SNP variations and functional effects that appear to be the way of the future for developing salinity-tolerant plants. Gene discovery to manipulate the molecular mechanisms which underlie the complex phenotype of salinity tolerance methods, identification of genes, QTL, association mapping, linkage, and functional genomics, such as transcript identifying and proteins related to salinity, is necessary. The present analysis also discussed some of the opportunities and challenges, focusing on molecular breeding strategies used in conjunction with other crop development approaches to growing elite salt-tolerant lines.

Genome resource of Xanthomonas oryzae pv. oryzae Chinese strain NE-8 causing bacterial blight of rice - Muhammad Sohaib Shafique; Wei Guo; Xifeng Chen; Kaijun Zhao; Yapei Liu; Chunlian Wang; Zhiyuan Ji (Functional & Integrative Genomics, 2023)

Managing plant density and nitrogen fertilizer to reduce nitrogen input without yield reduction of late-sown cotton after wheat by improving light interception and sink nitrogen partitioning in a double cropping system - Zhao Zhang; Shoaib Ahmed; Muhammad Sohaib Chattha; Anda Liu; Jiahao Liu; Na Lv; Lirong Yang; Xuefeng Ma; Xian'en Li; Feiran Hao; Guozheng Yang (Field Crops Research, 2023)

Isolation, characterization and larvicidal potential of indigenous soil inhabiting bacteria against larvae of southern house mosquito (Culex quinquefasciatus Say) - Sohaib Iftikhar; Muhammad Asam Riaz; Muhammad Zeeshan Majeed; Muhammad Afzal; Anam Ali; Mubshara Saadia; Zulfiqar Ali; Sohail Ahmed (International Journal of Tropical Insect Science, 2023)

Phytoremediation of Metal-Contaminated Soils and Water in Pakistan: a Review - Muhammad Shahbaz Akhtar; Ahmad Hameed; Sohaib Aslam; Razi Ullah; Aima Kashif (Water, Air, & Soil Pollution, 2023)

Designing a clean environmental framework for Pakistan: analyzing the nonlinear impact of aggregate demand drivers on CO2 emissions - Muhammad Afaq Haider Jafri; Huizheng Liu; Sana Ullah; Muhammad Tariq Majeed; Shahzad Anwar; Sohaib Mustafa (Environmental Science and Pollution Research, 2022)

Knowledge, attitude, and practice of clinicians about antimicrobial stewardship and resistance among hospitals of Pakistan: a multicenter cross-sectional study - Sohaib Ashraf; Shoaib Ashraf; Moneeb Ashraf; Muhammad Ahmad Imran; Zawar Ahmad Choudhary; Hadiqa Tul Hafsa; Abeer Bin Awais; Larab Kalsoom; Iqra Farooq; Zaighum Habib; Sidra Ashraf; Qurrat Ul Ain Iqbal; et al. (Environmental Science and Pollution Research, 2022)

Correction to: Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Ameliorative mechanisms of turmeric-extracted curcumin on arsenic (As)-induced biochemical alterations, oxidative damage, and impaired organ functions in rats - Anam Ishaq; Huma Gulzar; Ali Hassan; Muhammad Kamran; Muhammad Riaz; Aasma Parveen; Muhammad Sohaib Chattha; Noman Walayat; Sana Fatima; Sobia Afzal; Shah Fahad (Environmental Science and Pollution Research, 2021)

Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafiz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Phytochemical profiling, in vitro and in vivo anti-inflammatory, analgesic and antipyretic potential of Sesuvium sesuvioides (Fenzl) Verdc. (Aizoaceae) - M. Sajid-ur-Rehman; Saiqa Ishtiaq; Mohsin Abbas Khan; Meshal Alshamrani; Muhammad Younus; Ghazala Shaheen; Muhammad Abdullah; Ghulam Sarwar; Muhammad Sohaib Khan; Faraza Javed (Inflammopharmacology, 2021)

A research on conventional and modern algorithms for maximum power extraction from wind energy conversion system: a review - Muhammad Zeeshan Malik; Mazhar Hussain Baloch; Mehr Gul; Ghulam Sarwar Kaloi; Sohaib Tahir Chauhdary; Ali Asghar Memon (Environmental Science and Pollution Research, 2021)

Morpho-physiological Effects and Molecular Mode of Action of Mepiquat Chloride Application in Cotton: A Review - Shahbaz Atta Tung; Ying Huang; Abdul Hafeez; Saif Ali; Anda Liu; Muhammad Sohaib Chattha; Shoaib Ahmad; Guozheng Yang (Journal of Soil Science and Plant Nutrition, 2020)

First report of Curvularia verruculosa causing leaf spot disease of grape (Vitis vinifera) in Afghanistan - Nasir Ahmed Rajput; Hussainullah; Chao Huo; JiFen Cao; Muhammad Atiq; Rana Muhammad Atif; Abdul Mubeen Lodhi; Rehana Naz Syed; Sohaib Sarfraz; Akhtar Hameed; Zhijian Zhao (Journal of Plant Pathology, 2020)

Correction to: Sublethal effects of a juvenile hormone analog, Pyriproxyfen demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

Sublethal effects of a juvenile hormone analog, Pyriproxyfen on demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

A cross-sectional study of methicillin-resistant Staphylococcus aureus at the equine-human interface - Namra Waqar; Quratulain Amin; Tariq Munir; Muhammad Sohaib Ikram; Naveed Shahzad; Arkim Mirza; Arshad Ali; Muhammad Imran Arshad (Tropical Animal Health and Production, 2019)

First report of Geotrichum candidum causing postharvest sour rot of carrot in Punjab, Pakistan - Akhtar Hameed; Muhammad Waqar Alam; Abdul Rehman; Khalid Naveed; Muhammad Atiq; Nasir Ahmed Rajput; Sohaib Sarfraz; Nadia Liaqat; Faizan Ahmad Tahir (Journal of Plant Pathology, 2019)

First report of Alternaria alternata causing postharvest fruit rot of peach in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Aman Ullah Malik; Sidra Aslam; Mubeen Sarwar; Sajid Ali; Muhammad Arslan Khan; Akhtar Hameed; Sohaib Sarfraz (Journal of Plant Pathology, 2019)

Correction to: Preparation, optimization and pharmacological evaluation of 99mTc-4-hydroxy-3-(2-hydroxy-3-methoxybenzylideneamino) benzoic acid complex: as a novel potential radiopharmaceutical agent with hepatobiliary excretion - Muhammad Usman Akbar; Tanveer Hussain Bokhari; Samina Roohi; Khalid Mahmood Zia; Muhammad Razeen Ahmad; Saira Hina; Muhammad Sohaib (Molecular Biology Reports, 2018)

The use of PCR technique in the identification of Mycobacterium species responsible for bovine tuberculosis in cattle and buffaloes in Pakistan - Farah Akhtar; Muhammad Tariq Javed; Aziz-ur-Rehman; Muhammad Nisar Khan; Pervez Akhtar; Sayed Misdaq Hussain; Muhammad Sohaib Aslam; Razia Kausar; Mehwish Qamar; Monica Cagiola (Tropical Animal Health and Production, 2015)